Evaluation of Radiation Protection Practices and Patient Dose Reduction Strategies in Panoramic Imaging in Makassar, Indonesia - Rusli, Muhammad (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Panoramic radiography is an essential tool in dentistry, offering a wide field of view for diagnosis and treatment planning. However, it is associated with radiation exposure, necessitating the implementation of optimal radiation protection practices. This study aimed to evaluate radiation protection practices and patient dose reduction strategies employed in panoramic imaging facilities in Makassar, Indonesia. Methods: A cross-sectional study was conducted involving panoramic imaging facilities in Makassar. Data were collected through a combination of questionnaires, direct observations, and dosimetric measurements using thermoluminescent dosimeters (TLDs). The questionnaires assessed radiation protection practices, equipment specifications, and patient dose optimization strategies. Direct observations evaluated adherence to radiation protection protocols, while TLDs measured patient doses. Results: The study revealed variability in radiation protection practices and patient dose levels across different facilities. Some facilities demonstrated suboptimal adherence to radiation protection guidelines, including inadequate shielding and lack of proper collimation. Patient doses varied significantly, with some exceeding recommended levels. The study identified several factors associated with higher patient doses, including outdated equipment, lack of regular quality assurance programs, and limited awareness of dose optimization strategies. Conclusion: The findings highlight the need for improved radiation protection practices and patient dose optimization in panoramic imaging in Makassar. Implementing comprehensive quality assurance programs, regular equipment maintenance, and continuing education for dental professionals can contribute to minimizing radiation risks associated with panoramic radiography.